ANALYSIS OF THE IMPACT OF CORPORATE GOVERNANCE ON THE INSURANCE MARKET SERVICES (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2025)
This article analyzes the impact of corporate governance systems on the quality and efficiency of services in insurance companies. The main objective of the study is to determine the positive or negative effects of corporate governance mechanisms and principles on insurance market services. Using analytical, statistical, and comparative methods, the relationship between elements of corporate governance and customer service indicators was examined. The results indicate that a well-organized governance system enhances service efficiency and strengthens customer trust.